MyHomestay Application System for Booking and Approval - Khairiah Abd Aziz; Suhaila Mohd Yasin (Applied Information Technology And Computer Science, 2021)
MyHomestay Application System for Booking and Approval is an application that is developed for homestay booking that is specifically in Kota Tinggi, Johor district. Nowadays, many alternative applications allow homestay owner as a host to promote their homestay, but the fees incurred are substantial, between 14% to 20% of the total charges. On the other hand, the owner who is not willing to pay any fees may utilise their social media platforms to promote their homestay. But the inconsistency of the homestay description may confuse travellers or tourists in making the best decision. Currently, A&A World Vacation Sdn. Bhd., a travel and tours company that is based in Kota Tinggi, provides travel packages including hotel accommodations but has never promoted homestay residences. MyHomestay is an Android application that is developed according to Agile Model methodology and using Android Studio for application development, Firebase as the database and Windows 10 as the operating system. By developing this application, hopefully, the travel and tours company and homestay owners can use it as a solution to promote vacation options in the rural areas, particularly homestay businesses. Further, travellers and tourists can make a better decision before booking a homestay.